FATWA, AUTHORITY, AND DIGITAL TRADE: A Critical Legal-Discursive Analysis of Dropshipping Rulings in Indonesia and Egypt - Chakim, Lutfi; Hidayah, Nur; Hasanudin, Hasanudin (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
The development of the digital economy, which has given rise to new business models such as dropshipping, has sparked legal debates within Islam. This paper explores the legal and institutional dynamics shaping Islamic legal responses to dropshipping in the digital economy by conducting a comparative fatwa analysis between DSN-MUI (Indonesia) and Dār al-Iftā’ al-Miṣrīyah (Egypt). While both institutions seek to maintain Shariah integrity, their divergent conclusions DSN-MUI’s permissibility under a salam contract versus Dār al-Iftā’ al-Miṣrīyah ’s rejection under a murabahah framework reveal deeper ideological and contextual distinctions. Using critical constructivist discourse analysis, the study examines how fatwas reflect legal reasoning, power relations, regulatory objectives, and ideological orientations of fatwa-issuing bodies. The findings highlight the pluralism in Islamic economic jurisprudence and underscore the importance of contextual and policy-sensitive interpretations of Shariah in the evolving digital economy. The paper concludes with policy implications that advocate for empirical validation, cross-jurisdictional engagement, and doctrinally grounded innovation in contemporary fiqh al-muamalat. This study reveals the pluralism of dropshipping fatwa and the importance of contextual approaches and empirical validation in the development of Islamic economic fiqh in the digital era. Perkembangan ekonomi digital melahirkan model bisnis baru seperti dropshipping telah memunculkan perdebatan hukum dalam Islam. Penelitian ini mengeksplorasi dinamika hukum dan kelembagaan yang membentuk respons hukum Islam terhadap dropshipping dalam ekonomi digital dengan melakukan analisis fatwa komparatif antara DSN-MUI (Indonesia) dan Dār al-Iftā’ al-Miṣrīyah (Mesir). Sementara kedua lembaga berusaha untuk menjaga integritas Syariah, kesimpulan mereka yang berbeda izin DSN-MUI di bawah kontrak salam versus penolakan Dār al-Iftā’ al-Miṣrīyah di bawah kerangka murabahah mengungkapkan perbedaan ideologis dan kontekstual yang lebih dalam. Dengan menggunakan analisis wacana konstruktivis kritis, penelitian ini meneliti bagaimana fatwa tidak hanya mencerminkan penalaran hukum tetapi juga relasi kekuasaan, tujuan peraturan, dan orientasi ideologis badan penerbit fatwa. Temuan ini menyoroti pluralisme dalam yurisprudensi ekonomi Islam dan menggarisbawahi pentingnya interpretasi Syariah kontekstual dan sensitif kebijakan dalam ekonomi digital yang berkembang. Makalah ini menyimpulkan dengan implikasi kebijakan yang mengadvokasi validasi empiris, keterlibatan lintas yurisdiksi, dan inovasi yang didasarkan secara doktrin dalam fiqh al-muamalat kontemporer. Studi ini mengungkap pluralisme fatwa dropshipping dan pentingnya pendekatan kontekstual serta validasi empiris dalam pengembangan fiqh ekonomi Islam era digital.